Literacy development for efl learners: an instructional module for first-grade islamic junior high school students in west lombok regency - Jupri; Arif Rahman (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
Abstract This study investigated a promotion of literacy development for EFL learners. It was by presenting an instructional module for first-grade Islamic junior high school students in West Lombok Regency. This study studies investigated the importance of literacy development within the context of Islamic education as it enables students to engage with religious texts, participate in religious practices, and develop a stronger understanding of their faith. This study adopted a mix-method with a quantitative and qualitative research design with the involvement of survey and interviews to evaluate the effectiveness of the instructional module. This study also utilized a quasi-experimental research design, incorporating pre-test and post-test assessments, to thoroughly evaluate the effectiveness and impact of the instructional module designed in this study. An instructional module has been developed based on a set of criteria, including alignment with the Islamic junior high school curriculum, integration of religious and academic content, use of engaging and interactive instructional strategies, and incorporation of multimedia and technology-based elements. This study used a qualitative data through surveys and interviews with the participating teachers and students to gather their perceptions, feedback, and experiences with the instructional module. The quantitative data from the literacy assessments have been analyzed using appropriate statistical techniques, such as t-tests measures from SPSS statistical computation to determine the statistical significance of the changes in student literacy skills. The study revealed that the extent to which the instructional module has impacted students' literacy skills, including reading comprehension, vocabulary, and written expression. The qualitative data from the surveys, interviews, and observations provide insights into the teachers' and students' perceptions of the instructional module, its strengths, and areas for improvement. The statistical analysis showed a statistical significance of the changes in students’ literacy skills, allowing for a robust evaluation of the instructional module's effectiveness. Finally, this study presents a comprehensive examination of the design, implementation, and evaluation of an instructional module aimed at promoting literacy development in first-grade EFL learners within the context of Islamic Junior High School Schooling system.